1998
DOI: 10.1159/000025312
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Dystrophy: Centronucleation May Reflect a Compensatory Activation of Defective Myonuclei

Abstract: Muscular dystrophy has long been believed to be characterized by degeneration and abortive regeneration of muscle fibers (the muscle degeneration theory), but unfortunately its pathogenesis is still unclear and an effective treatment has yet to be developed. As a challenge to the theory, we have proposed an alternative muscle-defective-growth theory and a further bone muscle growth imbalance hypothesis supposing possible defects in bone-growth-dependent muscle growth based on our findings in hereditary dystrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The large percent area of regenerating fibers compared to other histopathological features indicates that the regenerative process is a substantial contributor to dystrophic muscle pathology. Studies detailing the process of muscle regeneration have shown that in damaged muscle tissue, fibers are capable of returning to normal fiber morphology; however, many regenerated fibers retain centrally located nuclei indefinitely 3639. The persistence of centrally located nuclei is believed to signify that abnormal processes are occurring in these cells that prevent the nuclei from returning to the periphery of the cell 3639.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large percent area of regenerating fibers compared to other histopathological features indicates that the regenerative process is a substantial contributor to dystrophic muscle pathology. Studies detailing the process of muscle regeneration have shown that in damaged muscle tissue, fibers are capable of returning to normal fiber morphology; however, many regenerated fibers retain centrally located nuclei indefinitely 3639. The persistence of centrally located nuclei is believed to signify that abnormal processes are occurring in these cells that prevent the nuclei from returning to the periphery of the cell 3639.…”
Section: Discussionmentioning
confidence: 99%
“…Studies detailing the process of muscle regeneration have shown that in damaged muscle tissue, fibers are capable of returning to normal fiber morphology; however, many regenerated fibers retain centrally located nuclei indefinitely 3639. The persistence of centrally located nuclei is believed to signify that abnormal processes are occurring in these cells that prevent the nuclei from returning to the periphery of the cell 3639. From this initial analysis, it was determined that for the GTE treatments muscle pathology should be examined at ages 28 and 42 days because these time points represent the early degenerative and regenerative disease stages.…”
Section: Discussionmentioning
confidence: 99%